In situ synchrotron stress mappings to characterize overload effects in fatigue crack growth. (April 2019) - Thielen, M.; Schaefer, F.; Gruenewald, P.; Laub, M.; Marx, M.; Meixner, M.; Klaus, M.; Motz, C.
Graphical abstract: Highlights: Clear experiment to measure crack tip stress fields at increasing load in synchrotron. Fatigue specimens before and some cycles after a mechanical overload cycle. Additionally, the stress fields have been measured in depth direction. Completes conventional XRD or digital image correlation affected by surface effects. The OL-sample with strong residual stress is related to the plastic zone of the OL. Abstract: The dominant retardation mechanism of fatigue cracks after an overload is still under discussion for modeling variable amplitude loading. Is it plasticity induced crack closure in the wake of the crack or the residual stress field in the K-dominated region in front of the crack? Over the thickness, fracture mechanics changes from plane stress to plane strain and consequently observations in different depths are essential. This has been realized by synchrotron measurements. We found the residual stress effect to be more dominant while stress gradients over the thickness are hardly found for the residual but for the applied stresses.